Low-intensity pulsed ultrasound enhances uptake of doxorubicin-loaded gold nanoparticles in cancer cells - Farshad Moradi Kashkooli; Anshuman Jakhmola; Graham A. Ferrier; Monika Lodyga; Kevin Rod; Jahangir (Jahan) Tavakkoli; Michael C. Kolios (Ultrasonics Sonochemistry, 2025)
The distinctive physicochemical properties of gold nanoparticles (AuNPs), such as biocompatibility, easy functionalization, and a high surface area-to-volume ratio, make AuNPs one of the most suitable candidates for cancer nanomedicine applications. However, achieving efficient uptake of drug-loaded AuNPs into cancer cells has remained a significant challenge in drug delivery. One promising non-invasive, pleiotropic modality that could enhance the cellular uptake of drug-loaded AuNPs by facilitating the transport through cell membranes is low-intensity pulsed ultrasound (LIPUS). This study employs cell experiments (viability and flow cytometry tests), finite element simulations, and dark-field/hyperspectral cell imaging to demonstrate that LIPUS significantly enhances the cellular uptake of doxorubicin-loaded AuNPs and free drug in cancer cells. The synergistic effects of low-intensity ultrasound and therapeutic agents further reduce cell viability, exceeding the effects of ultrasound or doxorubicin-loaded AuNPs alone. Driven by the thermal and mechanical mechanisms induced by LIPUS, this approach enhances endocytosis and sonoporation, thereby increasing cellular uptake of AuNPs and free drug through active and passive transport mechanisms. This results in a substantial improvement in treatment efficacy, marking a promising advancement in targeted drug delivery for cancer therapy.